Resilience Lessons From the Southeast United States Woody Pellet Supply Chain Response to the COVID-19 Pandemic† - Kline, Keith L.; Dale, Virginia H.; Rose, Erin (Frontiers in Forests and Global Change, 2021)
The Coronavirus Disease 2019 (COVID-19) instigated a pandemic that impacted economies, employment, and shipping worldwide. This paper reviews how one international supply chain performed and identifies lessons that may be helpful to improve future resilience. Economic and employment data through November 2020 are used to review the effects of COVID-19 on operations of the bioenergy supply chain in the southeastern United States (SE US) that utilizes wood fiber to fabricate pellets. Conditions associated with the production of pellets in the SE US changed with the outbreak of COVID-19. Federal and state government programs and classification of workers in this sector as “essential” during the pandemic helped maintain the woody pellet supply chain and other industries during a period of general shut down in 2020. The availability of personal protective equipment, long-term supply contracts, and established safety cultures are among the factors that enhance supply chain resilience while limited availability of skilled workers, inadequate stakeholder engagement, and dependence on external policies are among factors that reduce resilience. The analysis concludes with recommendations for the SE pellet supply chain, and other biomass supply chains, to improve their resilience to future disturbances. When best practices are implemented, SE US biomass offers opportunities to contribute to post-pandemic economic recovery while incentivizing better forest resource management.